STUDENTS’ DIFFICULTIES IN WRITING RECOUNT TEXT AT INCLUSION CLASSES - Husna, Atikasari; Multazim, Akhmad (LET: Linguistics, Literature and English Teaching Journal, 2019)
Writing skill is already taught in school and colleges. The students of Junior High School should retells something that already happened (Recount text). The objective of the study is to identify the students? difficulties in writing recount text in inclusion classes. The study belongs to a mixed-method research involving 30 students of 8th grade inclusion class. The data collecting techniques was testing. There were several steps to analyze the data: analyzing the students? work, calculating the average score by using descriptive statistic and the last step is descriptive analysis. The result of the study shows that the students? difficulties in writing recount text are related to content aspect, organization aspect, grammar aspect, mechanic aspect and generic structure of recount text aspect especially in orientation and reorientation.